PENERAPAN PRINSIP GCG (TRANSPARANSI & AKUNTABILITAS) DALAM KERANGKA LAPORAN KEUANGAN KELOMPOK PEMODAL 13 DI PONTIANAK TIMUR - Mardiyati, Mardiyati; Wahyudi, Hijrah (Jurnal Ekonomi STIEP ( JES ), 2018)
Purpose of this research is to know implication of GCG’s Principles (Transparency & Accountability) in Financial Statement’s framework of Kelompok Pemodal 13 in Pontianak Timur. This analysis is done by qualitative analysis in order to answer the research. The study conclude that implication of GCG’s Principles are important for Kelompok Pemodal 13 in order to construct their Financial Statement’s framework based on Standar Akuntansi Keuangan (SAK) and to raise credibility of stakeholders.